2014
DOI: 10.1016/j.devcel.2014.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Gene Expression through a Transcriptional Repressor that Senses Acyl-Chain Length in Membrane Phospholipids

Abstract: SummaryMembrane phospholipids typically contain fatty acids (FAs) of 16 and 18 carbon atoms. This particular chain length is evolutionarily highly conserved and presumably provides maximum stability and dynamic properties to biological membranes in response to nutritional or environmental cues. Here, we show that the relative proportion of C16 versus C18 FAs is regulated by the activity of acetyl-CoA carboxylase (Acc1), the first and rate-limiting enzyme of FA de novo synthesis. Acc1 activity is attenuated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
110
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 68 publications
14
110
1
Order By: Relevance
“…Moreover, a study reported that the knockout of SNF1 results in transcriptional pattern that differed from one on lipid accumulation devaluing the important role of this gene in lipid accumulation [69]. One alternative solution is to use hyperactive mutant Acc1 for higher malonyl-CoA production and consequently higher TAG accumulation, comprised of longer chain fatty acids, without need for snf1 inactivation [72]. This can contribute to a carbon flux re-direction from citric acid to lipid production.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study reported that the knockout of SNF1 results in transcriptional pattern that differed from one on lipid accumulation devaluing the important role of this gene in lipid accumulation [69]. One alternative solution is to use hyperactive mutant Acc1 for higher malonyl-CoA production and consequently higher TAG accumulation, comprised of longer chain fatty acids, without need for snf1 inactivation [72]. This can contribute to a carbon flux re-direction from citric acid to lipid production.…”
Section: Discussionmentioning
confidence: 99%
“…The kinase responsible for the human acetyl-CoA carboxylase phosphorylation is the AMP-activated protein kinase (AMPK) which in yeast is named Snf1p [8,9]. Snf1p/AMPK might not be the only kinase that regulates acetyl-CoA carboxylase activity, as in yeast, 30% of the Acc1p pool is phosphorylated in a snf1Δ background [10]. Protein phosphatase responsible for Acc1p dephosphorylation and subsequent activation remains unknown, although studies in mammalian and yeast models suggest that a PP2A-like protein phosphatase may be involved [11].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its metabolic role as a key intermediate in DAG, TAG, and phospholipid synthesis, PA also has signaling function, which operates through its specific interaction with the transcriptional repressor Opi1. This binding of Opi1 to PA regulates the subcellular distribution of the repressor and hence its nuclear repressing activity (Loewen et al 2004;Henry et al 2012;Hofbauer et al 2014).…”
Section: Glycerophospholipidsmentioning
confidence: 99%